TRANSPARANSI DAN TANTANGAN LAPORAN KEUANGAN DI PIMPINAN RANTING IKATAN PELAJAR NAHDLATUL ULAMA SIDOARJO - Putra, Alvine Syahrengga; Amrulloh Achmad Amin; Elfira Diah Asmawardani; Khafila Roudhotul Jannah; Sahrani, Lutfia; Audya, Meilynda Triana; Kholilulloh, Moch. Wildan; Safaro, Uci Silviatus; Zakariya, Novie Andriani (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This research aims to analyze the transparency of financial reports at PR. IPNU Desa Pepe Sidoarjo. Using a descriptive qualitative method, data was collected through semi-structured interviews, observation, and documentation. The results of this study indicate that PR. IPNU has implemented regular financial records, both manually through cash books and digitally with spreadsheets. All transactions are also supported by complete evidence that shows their commitment to the transparency of their financial reports.